RHEOLOGICAL PROPERTIES OF IRAQI ASPHALT BINDERS MEASURED USING SUPERPAVE SYSTEM AND SHELL SOFTWARE (Journal of Engineering, 2011)
The performance grading system (superpave) has provided means to incorporate binder characteristics withpavement failure types. It’s a comprehensive system that relates climate, traffic conditions and aging withcritical pavement distress. The objective of this paper is to develop an improved asphalt binder gradingsystem for Iraq based on the principal of superpave. The country was divided into different zones accordingto the highest and lowest temperature ranges and traffic loading. The Performance graded binder proposedfor each zone was compared with some States of USA that have same hot weather of Iraq by using LongTerm Pavement Performance (LTPP v3.1) software. Iraqi asphalt samples were tested using the Superpavetechnology in Wisconsin University and the results were compared with those estimated using Shellpavement design software packages (BANDS 2) at different loading time and frequency. In general, theperformance grade of binders produced from the three refineries in Iraq (Daurah, Basrah and Baiji) is PG 64-16. The m- value (slope of log creep stiffness versus log frequency curve at specified temperature)determined by DSR (Dynamic Shear Rheometer) and Shell software was compared.